2012
DOI: 10.1017/s0950268812002385
|View full text |Cite
|
Sign up to set email alerts
|

A survey of rodent-borne pathogens carried by wildRattusspp. in Northern Vietnam

Abstract: To examine the prevalence of human pathogens carried by rats in urban areas in Hanoi and Hai Phong, Vietnam, we live-trapped 100 rats in January 2011 and screened them for a panel of bacteria and viruses. Antibodies against Leptospira interrogans (22·0%), Seoul virus (14·0%) and rat hepatitis E virus (23·0%) were detected in rats, but antibodies against Yersinia pestis were not detected. Antibodies against L. interrogans and Seoul virus were found only in adult rats. In contrast, antibodies to rat hepatitis E … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 41 publications
3
13
0
Order By: Relevance
“…A study from Cambodia (2012) on Leptospira in rodents showed an overall infection of 11.1% (n = 642) (Ivanova et al, 2012) and a study from Malaysia found 11.0% (n = 357) , which correlates with our findings (13.1%), although we did not use a serological assay but a molecular assay. A serological study from Vietnam showed that 22% of trapped rodents host L. interrogans and all rodents were trapped in urban areas close to the South-China Sea and in Hanoi City, a city along the Red River (Koma et al, 2013). Research from 2003 conducted on the Andaman Islands showed a seroprevalence of 7.1% in R. rattus (n = 85) (Sharma, Vijayachari, Sugunan, & Sehgal, 2003), which again is in line with our findings (7.9%).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A study from Cambodia (2012) on Leptospira in rodents showed an overall infection of 11.1% (n = 642) (Ivanova et al, 2012) and a study from Malaysia found 11.0% (n = 357) , which correlates with our findings (13.1%), although we did not use a serological assay but a molecular assay. A serological study from Vietnam showed that 22% of trapped rodents host L. interrogans and all rodents were trapped in urban areas close to the South-China Sea and in Hanoi City, a city along the Red River (Koma et al, 2013). Research from 2003 conducted on the Andaman Islands showed a seroprevalence of 7.1% in R. rattus (n = 85) (Sharma, Vijayachari, Sugunan, & Sehgal, 2003), which again is in line with our findings (7.9%).…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies in Asia on rodents identify R. rattus to be the main reservoir host for human pathogenic Leptospira (Johnson et al, 2004;Ko et al, 1999;Sarkar et al, 2002). Other studies from Asia show varying numbers of infection percentages, ranging from 7.1%-22% Ivanova et al, 2012;Koma et al, 2013;Saravanan et al, 2000;Sharma et al, 2003).…”
Section: Leptospira Spp Prevalence In Wild Small Mammalsmentioning
confidence: 93%
“…The known animal reservoirs of HEV continue to multiply; novel members of the Hepeviridae have been detected in wild and farmed rabbits, wild rats, birds, bats, and trout (13,15,(88)(89)(90)(91)(92)(93)(94)(95)(96)(97)(98)(99)(100)(101)(102)(103)(104)(105)(106). Of these, only rabbit HEV strains have been shown to share a close phylogenetic relationship and possess antigenic similarity to human-and swine-associated HEV strains.…”
Section: Epidemiologic Patterns Of Hepatitis E Virus Infectionmentioning
confidence: 99%
“…In Japan, the rates were 31.5% (114/362) from 2000 through 2002, while another study with unreported sample collection dates resulted in 28.6% seroprevalence (16/56) [22,23]; in Germany, the seroprevalence was 24.5% (36/147) between 2007 and 2010 [24], comparable to China with 27.8% (64/230) between 2011 and 2012 [25]. In Vietnam, two separate studies revealed similar seroprevalences of 20.3% (25/123) and 22.3% (21/94) in 2011 and an additional study between 2012 and 2013 demonstrated a lower seroprevalence of 12.3% (48/389) [26][27][28]. In a recent study in Lithuania, the seroprevalence was 31.2% (34/109) between 2014 and 2017; however, data were derived from both Norway rats (27) and Black rats (82) and individual species rates were not indicated [29].…”
Section: Seroprevalence Of Anti-hev Antibodiesmentioning
confidence: 84%
“…In Vietnam, two separate studies revealed similar seroprevalences of 20.3% (25/123) and 22.3% (21/94) in 2011 and an additional study between 2012 and 2013 demonstrated a lower seroprevalence of 12.3% (48/389) [26][27][28]. In a recent study in Lithuania, the seroprevalence was 31.2% (34/109) between 2014 and 2017; however, data were derived from both Norway rats (27) and Black rats (82) and individual species rates were not indicated [29].…”
Section: Seroprevalence Of Anti-hev Antibodiesmentioning
confidence: 95%